"ANALYZING THE INFLUENCE OF A MODIFIED PHYSICAL EDUCATION CURRICULUM ON DEXTERITY AND SINISTRALITY IN 13-YEAR-OLD PRE-ADOLESCENT SCHOOL BOYS" (International Journal of Food and Nutritional Sciences, 2022)
The aim of this study was to assess the impact of a prototype physical education curriculum on the dexterity and sinistrality of 13-year-old preadolescent school boys. A total of 40 right-handed dominant preadolescent students from Government Higher Secondary School in Kulgam, Jammu and Kashmir, India, were chosen as participants for the study. These participants were divided into two groups, namely the experimental group and the control group, each comprising 20 subjects (n=20). The experimental group underwent the implementation of the model physical education curriculum, which consisted of four components: A (physical exercises), B (yogic asana), C (theoretical instruction), and part 'D' (recreational activities). The experimental group received training over a 15-week period, four days a week, with each class lasting 45 minutes, inclusive of warm-up and cool-down exercises. The visual reaction speed of both left and right hands served as the dependent variable and was assessed before and after the experimental period. Data collected were analyzed using ANCOVA, with a significance level set at 0.05. The findings indicate that the model physical education curriculum contributes to the enhancement of dexterity among preadolescent school boys